“Who Coverest with Light as a Garment…” Precious Metal Casings from the Collection of the Russian Museum: On the Problem of Formation, Artistic Originality, and Attribution - Pivovarova, Nadezhda V. (Actual Problems of Theory and History of Art, 2024)
The collection of the Department of Old Russian Art of the Russian Museum houses a comprehensive assortment of ecclesiastical artifacts, encompassing a wide array of precious, bas-relief, and chased rizas (oklads), in addition to a rich assortment of fragments derived from icons, Gospels, and crosses, dating from different historical periods.  The monuments date from the 14th to the end of the 19th century. Most part of them was transferred to the Russian Museum from the monastery sacristies (complexes of the Volokolamsky, Pokrovsky of Suzdal, Kirillo-Belozersky, Solovetsky, Alexander-Svirsky monasteries). In recent years, it has been possible to uncover new information about the additions and to expand the existing collection with the works from the sacristies of the Epiphany monastery in Kostroma, Annunciation monastery in Kirzhach, Alexander Nevsky monastery, and some others . The largest collection of fragments of rizas (chased plates from margins, plaques with inscriptions from icons, images of evangelists and compositions from the covers of the Gospels) were transferred to the Russian Museum from private collections of the 19th century. The largest number of items were drawn from the collections of M. P. Pogodin and N. M. Postnikov. As a result of the dismantling of valuable icon decorations during restoration work and their transfer to other departments of the museum, unidentified rizas emerged which were no longer associated with specific icons. All three categories of the aforementioned museum objects, with rare exceptions, have never been the subject of dedicated publications and require a comprehensive study.
Keywords: metal casings; icon; State Russian Museum; collection; inscription; attribution